Elevated CO2 Differentially Mitigated Oxidative Stress Induced by Indium Oxide Nanoparticles in Young and Old Leaves of C3 and C4 Crops - Ibrahim I. Shabbaj; Hamada AbdElgawad; Mansour A. Balkhyour; Abdurazag Tammar; Mahmoud M. Y. Madany (MDPI AG, 2022)
Soil contamination with indium (In) oxide nanoparticles (In2O3-NPs) threatens plant growth and development. However, their toxicity in plants under ambient (aCO2) and elevated (eCO2) conditions is scarcely studied. To this end, this study was conducted to investigate In2O3-NPs toxicity in the young and old leaves of C3 (barley) and C4 (maize) plants and to understand the mechanisms underlying the stress mitigating impact of eCO2. Treatment of C3 and C4 plants with In2O3-NPs significantly reduced growth and photosynthesis, induced oxidative damage (H2O2, lipid peroxidation), and impaired P and Fe homeostasis, particularly in the young leaves of C4 plants. On the other hand, this phytotoxic hazard was mitigated by eCO2 which improved both C3 and C4 growth, decreased In accumulation and increased phosphorus (P) and iron (Fe) uptake, particularly in the young leaves of C4 plants. Moreover, the improved photosynthesis by eCO2 accordingly enhanced carbon availability under the challenge of In2O3-NPs that were directed to the elevated production of metabolites involved in antioxidant and detoxification systems. Our physiological and biochemical analyses implicated the role of the antioxidant defenses, including superoxide dismutase (SOD) in stress mitigation under eCO2. This was validated by studying the effect of In2O3-stress on a transgenic maize line (TG) constitutively overexpressing the AtFeSOD gene and its wild type (WT). Although it did not alter In accumulation, the TG plants showed improved growth and photosynthesis and reduced oxidative damage. Overall, this work demonstrated that C3 was more sensitive to In2O3-NPs stress; however, C4 plants were more responsive to eCO2. Moreover, it demonstrated the role of SOD in determining the hazardous effect of In2O3-NPs.